Benefits and risks of ChatGPT in future education - Baltezarević Radoslav; Baltezarević Ivana (Megatrend Revija)
Created by OpenAI, ChatGPT is an artificial intelligence (AI) chatbot that makes use of natural language processing (NLP). ChatGPT analyses enormous volumes of data using machine learning (ML) to offer the necessary content and simply respond to queries in a conversational manner. Many industries, including healthcare, education, and finance, employ ChatGPT to increase productivity by automating a variety of language-related processes. In the context of education, ChatGPT helps professors and students cope with mental stress and complete assignments with greater efficiency. Professors can improve their pedagogical skills by creating and incorporating interactive classroom activities using ChatGPT's help. Additionally, ChatGPT assists researchers with data analysis, literature reviews, and grant application writing. Students can learn and develop in a variety of ways with ChatGPT thanks to individualized support, immediate feedback, and an extensive database of knowledge in a variety of areas. The tendency of ChatGPT to be excessively verbose, to provide assertions that are straightforward but incorrect, and to make assumptions about questions that are not quite apparent are some of its drawbacks. A further concern is that the rise of artificial intelligence (AI) chatbots, such as ChatGPT, has raised the possibility of plagiarism and cheating. Programs like GPTZero and CopyLeaks AI Content Detector have recently been created that are capable of effectively identifying these types of scams. Compared to its earlier iterations, the most cutting-edge publicly accessible model, ChatGPT 4, has improved understanding and is able to generate more complex responses with less bias.